Analyzing the effects of connecting Norway's remote communities to large cities using the Systems Thinking approach. Issue 1 (30th September 2020) - Witte, Caroline Saatvedt; Mansouri, Mo
Abstract: This paper explores how the Systems Thinking philosophy can be applied to determine the feasibility of significant infrastructure projects. Much too often, decisions are made without a thorough understanding of all the factors involved and their interrelations, as has been the case for many governmentally funded construction projects in Norway. The paper investigates the repercussions of connecting remote island villages to larger cities, by examining the short‐ and long‐term effects for two real‐life case studies And⊘rja and Lines⊘ya in Norway. The analysis is supported by a number of systems thinking tools, including a context diagram, stakeholder analysis, Systemigram to map user needs, and finally, leverage points to improve the decision‐making process are presented.